1996
DOI: 10.1006/viro.1996.0178
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HIV Infection by Pseudopeptides Blocking Viral Envelope Glycoprotein-Mediated Membrane Fusion and Cell Death

Abstract: The RP dipeptide motif is highly conserved in the third hypervariable region (V3 loop) of the extracellular envelope glycoprotein of different types of HIV isolates. In view of this, we have designed and synthesized a construction referred to as "template assembled synthetic peptide" (TASP), in which a lysine-rich short polypeptide was used as a template to covalently anchor arrays of tripeptides, such as RPR, RPK, or KPR. The pentavalent presentation, 5(RPR)-, 5(RPK)-, or 5(KPR)-TASP, molecules manifested max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 0 publications
3
54
0
Order By: Relevance
“…The pentavalent presentation, 5(RPR)-, 5(RPK)-, or 5[KPR]-TASP molecules, manifested maximum inhibitory activity on infection of cells by HIV-1 and -2 but not by simian immunodeficiency virus isolates, thus emphasizing the specific nature of these TASP inhibitors. In already infected cells, the TASP inhibitors also blocked syncytium formation and the occurrence of apoptosis (7). These observations indicated that these TASP inhibitors block a defined target that should be implicated in the functioning of the gp120⅐gp41 complex to initiate viral entry, syncytium formation, and apoptosis.…”
Section: Hiv 1 Is An Enveloped Virus That Infects Target Cells By Thementioning
confidence: 75%
See 3 more Smart Citations
“…The pentavalent presentation, 5(RPR)-, 5(RPK)-, or 5[KPR]-TASP molecules, manifested maximum inhibitory activity on infection of cells by HIV-1 and -2 but not by simian immunodeficiency virus isolates, thus emphasizing the specific nature of these TASP inhibitors. In already infected cells, the TASP inhibitors also blocked syncytium formation and the occurrence of apoptosis (7). These observations indicated that these TASP inhibitors block a defined target that should be implicated in the functioning of the gp120⅐gp41 complex to initiate viral entry, syncytium formation, and apoptosis.…”
Section: Hiv 1 Is An Enveloped Virus That Infects Target Cells By Thementioning
confidence: 75%
“…Structure and inhibitory activity relationship studies using analogs of 5[KPR]-TASP indicated that the two basic residues Lys and Arg in the tripeptide are essential and can be replaced by each other and that their positively charged side chains play a critical role in the inhibitory structure. Interestingly, replacement of Leu amino acid residues by Asp amino acids or the reduction of the peptide bond between the first two amino acids of the tripeptide generated pseudopeptide-TASP analogs active at submicromolar concentrations on HIV infection (7). By the use of FITC-and biotin-labeled 5[K⌿(CH 2 N)PR]-TASP constructs, we demonstrate here that the TASP inhibitors bind specifically to a 95-kDa, cell surface protein (p95).…”
Section: Hiv 1 Is An Enveloped Virus That Infects Target Cells By Thementioning
confidence: 95%
See 2 more Smart Citations
“…The expression of the nucleolin at the cell surface was illustrated by using a specific antagonist of nucleolin, the HB-19 pseudopeptide that was designed initially as a potent inhibitor of HIV infection [13][14][15][16]. HB-19 presents pentavalently the tripeptide KPR in which the peptide bond between the K and P is reduced in order to increase the endopeptidase resistance of this pseudopeptide.…”
Section: Expression Of Nucleolin At the Cell Surfacementioning
confidence: 99%